2018
DOI: 10.1002/clc.22883
|View full text |Cite
|
Sign up to set email alerts
|

NT‐proBNP is associated with mortality and adverse cardiac events in patients with atrial fibrillation presenting to the emergency department

Abstract: BackgroundAtrial fibrillation (AF) is the most common cardiac arrhythmia in the emergency department. The CHA2DS2‐VASc score helps to predict thromboembolic risk; however, the rate of other adverse cardiac events is more difficult to predict.HypothesisThe biomarker N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) has prognostic value in patients presenting to the emergency department with AF.MethodsDuring a 1.5‐year period, a prospective study was performed in consecutive patients presenting to the emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Briefly, our initial literature searches yielded 997 records, 37 of which were retrieved for full‐text assessment. Finally, 10 studies 10‐19 were included in this meta‐analysis. Figure 1 describes the detailed process of study selection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, our initial literature searches yielded 997 records, 37 of which were retrieved for full‐text assessment. Finally, 10 studies 10‐19 were included in this meta‐analysis. Figure 1 describes the detailed process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 11‐17 reported the association between BNP/NT‐proBNP level and MACEs risk. As shown in Figure 5, a fixed‐effect model meta‐analysis indicated that the pooled RR of MACEs was 2.17(95% CI 1.89–2.49) for the highest versus the lowest group of BNP/NT‐proBNP level, without heterogeneity between studies ( I 2 = 0.0%, P = .529).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports showed that the level of serum NT-ProBNP can be used to evaluate cardiac function in patients and provide a prognosis. 3,17) A combination of ACE inhibitor, β-blocker, and aldosterone antagonists without contraindications was recommended for patients of heart failure with reduced ejection fraction. 18) Even though patients with heart failure are treated with optimized ACEI, β-blocker, and aldosterone antagonists, almost 50% more cases of CHF are predicted by 2030.…”
Section: Discussionmentioning
confidence: 99%